Fusion of a Xylan-Binding Module to Gluco-Oligosaccharide Oxidase Increases Activity and Promotes Stable Immobilization - Vuong, Thu V.; Master, Emma R. (PLOS ONE, 2014)
The xylan-binding module Clostridium thermocellum CBM22A was successfully fused to a gluco-oligosaccharide oxidase, GOOX-VN, from Sarocladium strictum via a short TP linker, allowing the fused protein to effectively bind different xylans. The presence of the CtCBM22A at the N-terminal of GOOX-VN increased catalytic activity on mono- and oligo-saccharides by 2-3 fold while not affecting binding affinity to these substrates. Notably, both GOOX-VN and its CBM fusion also showed oxidation of xylo-oligosaccharides with degrees of polymerization greater than six. Whereas fusion to CtCBM22A did not alter the thermostability of GOOX-VN or reduce substrate inhibition, CtCBM22A_GOOX-VN could be immobilized to insoluble oat spelt xylan while retaining wild-type activity. QCM-D analysis showed that the fused enzyme remained bound during oxidation. These features could be harnessed to generate hemicellulose-based biosensors that detect and quantify the presence of different oligosaccharides.